Relationship between Nutritional Status and the Incidence of Anemia among Children Aged 6 Months - 3 Years - Retno Setyo Iswati; Desta Ayu Cahya Rosyida (Proceeding of International Conference on Science, Health, And Technology, 2019)
Less nutritious foods that are and poor food variations can cause a lack of nutrients causing health problems, one of which is anemia. Anemia causes lack of oxygen intake to body tissues, especially brain tissue. Lack of oxygen to the brain tissue among under-five children can result in decreased cognitive function and it can inhibit growth and psychomotor development. Anemia in children can also interfere with the immune system so the children are susceptible to infectious diseases. To determine the relationship between nutritional status and the incidence of anemia among children aged 6 months - 3 years. This was an observational analytic study with cross sectional approach. The study population was children aged 6 months - 3 years amounting to 30 children. The sampling used total sampling technique. The variabel of age of nutritional status was divided into 2 groups, namely good nutrition and undernutrition. It was said to be good nutrition if the nutritional status was in -2SD up to 2 SD and undernutrition if the nutritional status was from -3 SD to <-2SD. Furthermore, the variable of the incidence of anemia was divided into 2 groups, namely had anemia and did not have anemia. The child was said to had anemia if the hemoglobin level was <11 gr% and the child was said to did not have anemia if the hemoglobin level was ≥11 gr%. The instrument used to determine the nutritional status was a a Z-score table, while hemoglobin levels were measured using a haemometer using peripheral blood. Data analysis was performed using the Chi Square test. The results of analysis on the nutritional status showed that most of respondents namely 25 people (83.3%) had good nutritional status and 5 people had undernutrition status (16.7%), while the incidence of anemia showed that the majority of respondents were not anemic of 93.3% and 2 people were anemic (6.7%) Bivariate analysis showed that of all respondents with good nutritional status as many as 25 people, all were not anemic (83.3%); while of 5 people with undernutrition status, 3 people were not anemic (10%) and 2 people were anemic (6.7%), p=0.001<α=0.05 which indicated that there was a significant relationship between nutritional status and the incidence of anemia. There was a relationship between nutritional status and the incidence of anemia.